الهوية الرقمية وتشكل العائلة الالكترونية دراسة أثنوغرافية للهوية اللادينية - رقية عطر; نور الهدى تماسيني (جامعة الوادي - University of Eloued, 2025)
"تهدف هذه الدراسة إلى فهم كيفية تشكيل الأفراد لهوياتهم الرقمية مقارنة بهوياتهم الواقعية، وتأثير ذلك على تعبيرهم عن توجهاتهم اللادينية في السياقات الرقمية. بحيث تمت دراسة دور العلاقات الاجتماعية الإلكترونية، وخاصة العائلة الإلكترونية في مجموعات الفيسبوك في توفير الدعم النفسي والاجتماعي ومدى تأثيرها على تشكيل الهوية الشخصية والقيم المشتركة بين الأفراد. كما تم تحليل دور المنصات الرقمية كمساحة آمنة أو كمصدر للتهديد في التعبير عن اللادينية، وكيفية تكيف الأفراد مع التوقعات الاجتماعية التقليدية في ظل الهوية اللادينية. كما اكتسبت الدراسة أهمية كبيرة في فهم تأثير التكنولوجيا على الهويات والقيم والتوجهات الفكرية، إذ تبرز التحديات التي تواجه الأفراد في التعبير عن أنفسهم بحرية، وتسلط الضوء على الدور المتزايد للمجتمعات الإلكترونية في تقديم الدعم النفسي والاجتماعي. كما تركز على الأقليات اللادينية في الجزائر، مما يجعلها مرجعا مهما للدراسات الأكاديمية المستقبلية في مجال علم اجتماع الاتصال. وللبدء في غمار هذه الدراسة قمنا بطرح التساؤلات التالية :كيف تساهم البيئة الرقمية في تشكيل الهوية اللادينية للأفراد، وكيف يتم تكوين ""العائلة الالكترونية "" التي تمثل هذه الهوية خارج السياقات الاجتماعية الدينية التقليدية؟ وما الدور الذي تلعبه هذه الهوية في تعزيز الوعي الذاتي والتفاعلات الاجتماعية للأفراد ضمن هذه الفضاءات الرقمية؟ كما اعتمدنا في دراستنا على المنهج الاثنوجرافي، وتم استخدام اداة المقابلة الإلكترونية لجمع البيانات من عينة بلغت 30 فردا من اللادنيين مستخدمي مجموعات الفيسبوك الخاصة بالجزائريين، بحيث تم الاستناد على مقاربتين نظريتين هما نظرية الأداء والهوية ونظرية ما بعد الإنسانية. وفي الأخير توصلت الدراسة الى عدة نتائج أهمها أن العائلة الإلكترونية تشكل منصة حيوية لتعزيز الهوية الرقمية، مما يسهم في تعزيز الوعي الذاتي وتسهيل التفاعلات الاجتماعية. كذلك، بينت الدراسة كيف يمكن للفضاءات الرقمية أن تعيد تشكيل العلاقات الاجتماعية خارج السياقات التقليدية، مما يعكس أهمية العائلة الإلكترونية كمجتمع يتشارك القيم والتوجهات. "This study aims to understand how individuals form their digital identities compared to their real-life identities, and the impact this has on their expression of non-religious orientations in digital contexts. The role of online social relationships, particularly online families in Facebook groups, in providing psychosocial support was examined, as well as their impact on shaping personal identity and shared values. The role of digital platforms as a safe space or a source of threat in expressing non-religion was also analyzed, as was how individuals adapt to traditional social expectations in light of their non-religious identity. The study has also gained significant importance in understanding the impact of technology on identities, values, and intellectual orientations, as it highlights the challenges individuals face in expressing themselves freely and sheds light on the growing role of online communities in providing psychosocial support. It also focuses on non-religious minorities in Algeria, making it an important reference for future academic studies in the field of sociology of communication. To begin this study, we posed the following questions: How does the digital environment contribute to shaping individuals' non-religious identities, and how is the ""online family"" that represents this identity formed outside of traditional religious social contexts? What role does this identity play in enhancing self-awareness and social interactions within these digital spaces? Our study also relied on an ethnographic approach, using an electronic interview tool to collect data from a sample of 30 non-religious individuals who use Facebook groups for Algerians. The study relied on two theoretical approaches: the theory of performance and identity and the theory of posthumanism. Ultimately, the study reached several conclusions, the most important of which is that the electronic family constitutes a vital platform for strengthening digital identity, which contributes to enhancing self-awareness and facilitating social interactions. The study also demonstrated how digital spaces can reshape social relations outside of traditional contexts, reflecting the importance of the electronic family as a community that shares values and orientations. "
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع الاتصال
Keywords: فيسبوك; الهوية اللادينية; العائلة الالكترونية; الهوية الرقمية; Digital identity; Electronic family; Non; religious identity; Facebook